An Agent-Mediated Knowledge Management System in Call Centers Using SMV and TROPOS - Kaveh Pashaei; Fattaneh Taghiyareh; Farzad Peyravi (International Journal of Information and Communication Technology Research, 2009)
Call centers have become one of the most cost effective ways of selling products to customers and giving services to them in different industries. By applying knowledge management solutions, we can meet call centers' challenges and gain benefits of reduced training costs, improved call handling and greater flexibility. This paper describes an agent mediated knowledge management system in call centers using the Tropos methodology. We use structure-in-5 for architectural design which specifies that our KM system is an aggregation of five sub-structures. Furthermore we develop a formal methodology and technique to verify the validity of communication protocols defmed in a multi-agent environment. This is accomplished by examining agent conversations before deploying the system. The methodology leads to the definition of six different classes of agents. Our experiments develop proof of concept module for a call center that automatically verifies some of the important properties identified in this methodology. Results prove the agent's specification and indicate that our proposed model works accurately. The paper concludes with observations on the call centers and the role of agents in the proposed model.